Handheld multi‐modal imaging for point‐of‐care skin diagnosis based on akinetic integrated optics optical coherence tomography. Issue 10 (3rd August 2018) - Sancho‐Durá, Juan; Zinoviev, Kirill; Lloret‐Soler, Juan; Rubio‐Guviernau, Jose Luis; Margallo‐Balbás, Eduardo; Drexler, Wolfgang
Abstract : A handheld skin imaging system with joint optical coherence tomography (OCT) at 1300 nm and digital epiluminescence microscopy (EM) is presented. The 2 modalities are physically co‐registered in a common‐path configuration. The instrument is enabled by a dedicated planar lightwave circuit with a footprint of only 1.1 × 19.5 mm 2 that provides akinetic axial OCT scanning at speeds up to 24 kHz. Lateral scanning is implemented through a low‐voltage Micro Electro‐Mechanical System (MEMS) mirror packaged with the axial scanner in a hermetic butterfly module. The OCT system, with a volume of only 80 × 27 × 14 mm 3, achieves an isotropic resolution of ~11 μm in tissue, −93 dB sensitivity, 12 mm lateral field of view, and an axial scanning range of 2.8 mm in air. The complete battery‐powered device has a weight of 3 kg in a tablet format, enabling point‐of‐care use cases. This work shows that integration of complementary imaging modalities through miniaturization technology results in clinically valuable instruments supporting a patient‐centered diagnostic imaging workflow. Abstract : A handheld skin imaging system with joint optical coherence tomography (OCT) at 1300 nm and digital epiluminescence microscopy is presented. The instrument is enabled by a dedicated planar lightwave circuit (1.1 × 19.5 mm 2 footprint) providing akinetic axial OCT scanning. The OCT engine (80 × 27 × 14 mm 3 in volume), achieves ~11 μm of isotropic resolution in tissue, −93 dB sensitivity, 12 mm field of view, and 2.8 mm axial scanning range in air.